A STUDY ON VOCABULARY FREQUENCIES IN TEXTBOOKS FOR TEACHING TURKISH TO FOREIGNERS (Third Sector Social Economic Review, 2023)
Learning a language different from the mother tongue offers an individual the opportunity to look at life from different perspectives and engage in new experiences. Teaching Turkish as a foreign language (TTFL) has been given more importance in recent years with the increase in the number of people coming to Turkey from different countries for various reasons, and thus the diversity of studies in this field has increased. The more audio-visual and written materials are introduced into the classroom environment, the more the learners’ vocabulary and conceptual world will develop. However, these should not be expected from every teacher, so there is a need for language teaching textbooks to have a qualified structure. A great care should be taken for textbooks to appeal to the age group of learners, for texts in these textbooks to include carefully selected words and for textbooks to develop vocabulary in students to the greatest extent because textbooks are given great responsibility in helping learners to develop their vocabulary. There are many textbooks belonging to different institutions and organizations used in TTFL. Word frequency studies will contribute to the formation of vocabulary, to get an idea about the development process of the language, to make text analysis healthier and to understand the cultural change based on words. The purpose of the current study is to determine the total number of words and the number of unique words in the texts included in the Gazi Turkish for Foreigners and İstanbul Turkish for Foreigners A1, A2, B1, B2 and C1 level textbooks.
Keywords: Language teaching; teaching Turkish to foreigners; vocabulary teaching; word frequencies.